A new class of epitaxial porphyrin metal–organic framework thin films with extremely high photocarrier generation efficiency: promising materials for all-solid-state solar cells. Issue 33 (2nd August 2016) - Liu, Jinxuan; Zhou, Wencai; Liu, Jianxi; Fujimori, Yamato; Higashino, Tomohiro; Imahori, Hiroshi; Jiang, Xue; Zhao, Jijun; Sakurai, Tsuneaki; Hattori, Yusuke; Matsuda, Wakana; Seki, Shu; et al.
Abstract : A new class of epitaxial porphyrin metal–organic framework thin films were fabricated and demonstrated to be promising materials for all-solid-state solar cells. Abstract : We demonstrate the fabrication of a new class of epitaxial porphyrin metal–organic framework thin films whose photophysical properties can be tuned by the introduction of electron-donating diphenylamine (DPA) groups into the porphyrin skeleton. The attachment of DPA groups results in strongly improved absorption characteristics, yielding the highest photocarrier generation efficiency reported so far. DFT calculations identify a shift of the charge localization pattern in the VBM (lowest unoccupied molecular orbital), confirming that the introduction of the DPA groups is the main reason for the shift of the optical absorption spectrum and the improved photocurrent generation.